Use of grape pomace as a fine aggregate in concrete - Adam, Christopher (Department of Civil Engineering, 2025)
The construction industry utilizes significant quantities of natural resources, which is most evident in the production of concrete. With the global shift towards sustainable construction materials and techniques, research has been conducted into the replacement of cement or aggregates with alternative materials. These alternatives range from recycled glass, plastic, rubber, hemp, and sawdust, to other organic materials. Minimal research has been conducted into the use of pomace in concrete. Grape pomace is a waste by-product from the six-stage wine-making process comprising skins, stalks, and seeds. Stalks are removed during destemming at stage two while white grape pomace is removed after the pressing process, stage 3, and red grape pomace after the fermentation process, stage 4. The waste is generated annually during the harvest season and is currently either used as a conditioner in the vineyards or taken to landfill sites. The abundance of pomace in the Western Cape of South Africa necessitates the need for the valorisation of the material with the focus of this research being the partial replacement of fine aggregate in concrete with grape pomace. Grapes are the most abundant crop globally with the highest wastage factor of approximately 20% when used for winemaking. Red grape pomace from a single source in Stellenbosch, South Africa, was used as white grapes are expected to contain sugars that may retard the setting of the concrete. The stalks were omitted from the pomace and only the seeds and skins were oven dried and ground from a particle size of 3 to 5 mm down to 0.6 to 2.4 mm. Fine aggregate in concrete aids the binding of cement, water, and coarse aggregate, increasing workability, limiting shrinkage, and reducing the cement content required to fill the voids between the coarse aggregate. Philippi dune sand was used as the fine aggregate in the concrete mix design and was replaced with the dried and ground pomace by volume at 5, 10, 15, 20, and 30%. Specimens were cast in the laboratory and cured in a temperature-controlled water bath and compression testing performed at 1, 7, 14, 28, and 56 days. Water absorption testing was performed on the pomace multiple times and the results were deemed unreliable, for this reason, the mix water quantity was kept constant in all the specimens and no adjustment was made for absorption. The slump testing displayed the effects of water absorption on the pomace with the slump decreasing with an increase in pomace content. The compressive strength testing highlighted that an increase in pomace content resulted in a decrease in compressive strength. Two pomace specimens, 5 and 10% achieved the design strength of 25 MPa after 28 days while the control specimen achieved 1.5 times the design strength after the same 28-day period. The remaining pomace specimens all failed to reach the design strength after 28 days with the lowest strength recorded at 18.2 MPa after 28-days. It is expected that the material properties of the grape pomace, having a lower specific gravity to the fine aggregate, were the cause of the reduction in the slump, lower density, and reduced compressive strength. The density reduction is attributed to the differing material densities between the pomace and fine aggregate, while the slump variation is because of the pomace's absorption of available mix water. The pomace particles aided the mechanical interlock while blocking the bleed water resulting in a weaker bond between the cement paste and aggregates causing the concrete specimens to experience a reduction in compressive strength. Furthermore, the low pH of the pomace could be causing an unstable environment restricting the microstructure development. Concrete is designed for a specific compressive strength requiring a certain water-to-cement ratio. The experimental testing highlighted that pomace, even at low replacement percentages, significantly reduced the compressive strength of concrete. To achieve a 25 MPa pomace concrete, the water-to-cement ratio would have to be lowered resulting in an increased cement content. The pomace content would need to be a minimum of 30% and yield similar results to the control specimen to justify its use. Pomace is not deemed to be a suitable replacement for fine aggregate in concrete as it results in inferior concrete, is uneconomical, and increases the concrete's carbon footprint.